Trials and Confessions of a Housekeeper - Arthur, T. S. (Timothy Shay), 1809-1885 (Salt Lake City, UT : Project Gutenberg, 2003)
"Trials and Confessions of a Housekeeper" by T. S. Arthur is a collection of narratives centered on the personal experiences of a housekeeper, written during the mid-19th century. The book explores the everyday struggles, challenges, and humorous incidents of managing a household, with a focus on domestic life and the moral dilemmas that can arise, reflecting the author's perspectives on social responsibility and personal growth. At the start of the book, the protagonist recounts a formative experience shortly after her marriage, highlighting her aspirations for elegance and beauty in her home despite financial constraints. This leads to a fateful decision to trade her husband's old coat for beautiful china vases from a street vendor, a decision that she later regrets when she realizes how much better that coat could have served a struggling neighbor in need. This narrative vividly sets the tone for the book, which interweaves practical insights about housekeeping with moral lessons on generosity, empathy, and the true meaning of wealth, seen through the eyes of a dedicated homemaker navigating the complexities of family and society. (This is an automatically generated summary.)
Release date is 2003-11-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Housekeeping -- Fiction; Housewives -- Fiction; Home economics -- Fiction